Utility of apremilast in the treatment of psoriasis - Snehalatha, K.; Ravindranathan, Roshni; Sriram, D. K.; George, Melvin (International Journal of Basic & Clinical Pharmacology, 2018)
Psoriasis is an autoimmune disease that affects more than one bodily system with predominantly skin and also joint manifestations affecting almost 2% of the world population that occurs primarily due to immune dysregulation. Apremilast is an oral, selective inhibitor of phosphodiesterase-4 (PDE4) enzymes. Inhibition of PDE-4 results in specific elevation of cAMP, an innately occurring intracellular secondary messenger that functions as a modulator of inflammatory responses. The drug is taken orally in strengths of 10, 20 and 30 mg. The drug may be a suitable alternative to different systemic therapies. Apremilast is a much-needed molecule for the treatment of psoriasis that is resistant to first line therapy and also useful in combination therapies.